THE ROLE AND IMPORTANCE OF INNOVATION IN ENTREPRENEURSHIP (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Entrepreneurship and innovation are one of the important factors in the development of the global economy today. The introduction of innovations into business activities not only increases the efficiency of the organization, but also stimulates the creation of new markets, new products and services. This dissertation provides information about the role of innovation in business.